The Effect of the Implementation of Mobile Asset Management in Asset Administration on the Discipline of Asset Users in the Office of Population Control Family Planning Empowerment of Women Child Protection of Sukabumi City - Farida, Fida; Purwanti, Dian; Mulyadi, Andi (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze the influence of the implementation of movable asset management in asset administration on asset user discipline at the Office of Population Control, Family Planning, Women Empowerment, and Child Protection in Sukabumi City. The research background highlights the administrative irregularities in regional asset utilization that hinder accountability and public service efficiency. A descriptive quantitative approach was employed, using a saturated sampling technique involving 100 respondents. Data were collected through questionnaires, observation, interviews, and literature studies. Simple linear regression analysis results indicate a positive and significant influence of movable asset management on user discipline, with a determination coefficient of 68.4%. This suggests that improved asset management through inventory, legal audits, valuation, utilization, and monitoring correlates with higher employee discipline in accountable and orderly asset use. The findings reinforce the importance of systematic asset governance in fostering a culture of discipline within local government institutions.